The The Impact of Flouting Grice Maxims toward Communication Purpose Used by The Main Characters of Mr. Iglesias the American TV Series (Universitas Negeri Semarang, 2021)
Cooperative Principle (CP) plays an important role in communication since it can guide people to achieve meaningful communication without misunderstanding. In reality, people do not always obey the rule or maxims of Cooperative Principle when they are having a conversation. The speakers sometimes deliberately flout the maxims because they want to convey the implicit meaning behind their utterances. The point of this research is to explain the flouting of maxims during the conversations in Mr. Iglesias TV series. Besides, this research also tries to discuss the impact of flouting maxims. This research is conducted by using a descriptive qualitative method based on the theory of Cooperative Principle proposed by Grice (1975). The data are in the form of utterances used by the main characters in Mr. Iglesias TV series. The findings reveal that there are four types of flouting maxims used by the characters, namely flouting maxim of quantity, flouting maxim of quality, flouting maxim of relation, and flouting maxim of manner. Besides, I also found the impacts of flouting maxims toward communication purpose such as creating humor, producing figurative language, and expressing emotions. In conclusion, the flouting maxims occur because it is one of the ways to make communication goes smoothly.